MODUL PEMBELAJARAN IPA TERPADU PADA MATERI TANAH DAN KEBERLANGSUNGAN KEHIDUPAN - ELVI RAPILUS; BASA T RUMAHORBO; VIRMAN VIRMAN (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2019)
Science learning modules on soil material and life sustainability have never been made especially in SMP Negeri 2 Manokwari. This research is a research and development (Research & Development) that aims to find out how to make integrated science modules, the feasibility of integrated science modules, and increase learning outcomes in soil material and the sustainability of life. The research sample was carried out in class IX E SMP Negeri 2 Manokwari with a total of 38 students. The results of the study show that: 1) The method of developing an integrated science module based on guided inquiry on soil material and life sustainability starts with the stages of definition, module planning, module draft design, and development. from the validator of 88% in the very feasible category, science teachers by 90% in the very feasible category, and the results of small-scale trials by 89%. 3) Increasing student learning outcomes with an average pretest score of 35.72 to 71.11 in the posttest and n-gain tests an average of 0.55 in the medium category.